ANALISIS KIMIA DAN DESTILASI KERING KAYU KARET - Sri Komarayati; Dadang Setiawan; Tjutju Nurhayati (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
This paper deals with chemical and charcoal properties of rubberwood. The analysis of chemical propertis comprises of the determination of cellulose, holocellulose, lignin, pentosan, moisture content, ash content, silica content, solubility in cold water, hot water, sodium hydroxide 1 percent and ethanol-benzene (1 : 2). The analysis of charcoal property comprises of charcoal, tar, pyroligneous liquor, calorific value, volatile matter and fixed carbon.The result showed that cellulose content 48.38 % - 50.26 % ; holocellulose 59.68 % -60.17 % ; lignin 31.33 % - 33.49 % ; pentosan 15.98 % - 16.43 % ; moisture content 7.34 -9. 98 % ; ash 0. 64 - 0. 71 % ; silica 0. 57 % - 0. 60 %. Solubility in cold water 2. 39 % - 4.48 %; in hot water 3.33 % - 5.93 % ; in alcohol-benzene (1 : 2) 2.35 % - 2.37 % and in one percent sodium hydroxide 18. 87 % - 20. 72 %.Based on chemical analysis, especially the cellulose and pentosan content, rubberwood is suitable as raw material forpulp and paper, rayon andfiberwood.Chemical analysis of charcoal indicated that charcoal yield variedfrom 28.16 % - 29. 77 % ; tar 6.86 % - 7.4666 % ; pyroligneous liquor 87.50 - 103.23 % ; calorific value 7114.68 cal/gr -7166. 77 cal/gr .fixed carbon 73.82 % - 78.05 % and volatile mailer 20.45 % - 23. 61 %. Proximate analysis of charcoal obtained from this experiments revealed that the quality are suitable for commercial charcoal, metallurgy charcoal and as raw malerial of activated charcoal.